2007
DOI: 10.1002/mrd.20782
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cAMP on the first mitotic cell cycle of mouse embryos

Abstract: Mitosis promoting factor (MPF) plays a central role during the first mitosis of mouse embryo. We demonstrated that MPF activity increased when one-cell stage mouse embryo initiated G2/M transition following the decrease of cyclic adenosine 3', 5'-monophosphate (cAMP) and cAMP-dependent protein kinase (PKA) activity. When cAMP and PKA activity increases again, MPF activity decreases and mouse embryo starts metaphase-anaphase transition. In the downstream of cAMP/PKA, there are some effectors such as polo-like k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some Setdb1 m−z+ embryos went through the first cleavage division, but these embryos displayed chromosome segregation defects. Given that the meiosis-to-mitosis transition is mechanistically a gradual process lasting over many cleavage divisions (Courtois et al, 2012;Cui et al, 2008;Poueymirou and Schultz, 1987;Yu et al, 2008), we propose that the observed defects in G2/M transition and mitosis underlie the arrest of Setdb1 m−z+ embryos at successive stages of preimplantation development.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some Setdb1 m−z+ embryos went through the first cleavage division, but these embryos displayed chromosome segregation defects. Given that the meiosis-to-mitosis transition is mechanistically a gradual process lasting over many cleavage divisions (Courtois et al, 2012;Cui et al, 2008;Poueymirou and Schultz, 1987;Yu et al, 2008), we propose that the observed defects in G2/M transition and mitosis underlie the arrest of Setdb1 m−z+ embryos at successive stages of preimplantation development.…”
Section: Discussionmentioning
confidence: 93%
“…Interactions between microtubules and kinetochores on chromosomes ensure proper chromosome segregation (Watanabe, 2012). Following fertilization, embryonic cleavage divisions share initially common mechanisms with meiosis such as a cAMP-PKA-dependent nuclear envelope breakdown (NEBD) and MTOC-driven bipolar spindle formation (Courtois et al, 2012;Cui et al, 2008;Poueymirou and Schultz, 1987;Yu et al, 2008). The organization of spindles gradually transitions over eight cleavage divisions from a large meiotic spindle into a short mitotic spindle harboring centrosomes (Courtois et al, 2012;Kubiak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that MPF is a critical regulator of early embryo development in mice (Yu et al, 2005(Yu et al, , 2008. This factor is composed of a catalytic subunit, Cdc2, with a histone H1 kinase activity and a regulatory subunit, cyclin B (King et al, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After its entry, HCO 3 − has been shown to activate the downstream cAMP-dependent pathway in a number of cell types via its sensor, the soluble adenylate cyclase (sAC) [33]. Interestingly, it has been shown that cAMP activation is essential for embryo development [34] and both CFTR and sAC are expressed in preimplantation embryos [5] (Supplementary information, Figures S1 and S2), suggesting their possible involvement in mediating HCO 3 − -dependent cAMP signaling in preimplantation embryo. Given the recently revealed role of miR-125b in embryo development of lower organisms, we proposed that the high HCO 3 − content present in the female reproductive tract may exert its effect on embryo development by regulating miR-125b expression via CFTR-mediated cAMP pathway.…”
Section: Hcomentioning
confidence: 99%